Quinine levels in patients with uncomplicated falciparum malaria in the Amazon region of Brazil - Vieira,José Luiz Fernandes (2008)
We examined the plasmatic concentrations of quinine in patients with uncomplicated falciparum malaria in an endemic area of the Amazon region in Brazil in a prospective clinical trial, in which a standard three-day course of oral quinine plus doxycycline was used. We measured the quinine in the plasma samples on days 0 and 3by high performance liquid chromatography. The mean concentration of quinine was 6.04 ±2.21 µg/mL in male patients and 5.98 ±1.95 µg/mL in female patients. No significant differences in quinine concentration were observed between these two groups. All samples collected before starting treatment were negative for quinine. This information could help in the development of strategies for the rational use of antimalarial drugs in Brazil.